Medical Science of Milk Included in Celsus’ Treatise De medicina - Kokoszko, Maciej; Dybała, Jolanta (Studia Ceranea, 2016)
Milk was a very significant food product in the Mediterranean. The present study is not devoted to milk as such, but to therapeutic galactology, galaktologia iatrike (γαλακτολογία ἰατρική), a version of which is extant in De medicina penned by a Roman encyclopaedist called Celsus. The author places milk and milk-derived products among therapeutic substances, indicates the methods of processing such substances, and also provides the readers with details on dietary and pharmacological characteristics of dairy foods as well as indicating their place in a number of cures. It is necessary to pay attention to the fact that the characterizations of milk and dairy products with regard to their dietary properties and application as pharmakon (φάρμκον) are not an exclusive feature of De medicina, but they are regularly mentioned not only in medical works, such as De diaeta I–IV, teachings of Dioscorides, extant fragments penned by Rufus of Ephesus, Galen, Oribasius, Aetius of Amida and Paul of Aegina, but also in Historia naturalis by Pliny. This is a clear sign that milk was considered to be significant from the medical point of view and was as such very interesting both for the medical profession and for general public. Therefore De medicina appears as a typical work, and details contained in it are simply a testimony of the evolution of the doctrine that was already present in De Diaeta I–IV and later developed by the most prominent physicians.